Caustic oesophageal stricture treated by instrumental dilatation: A review of 6 years of practice at the pediatric university hospital charles de gaulle of Ouagadougou - Ouedraogo Somkieta Francis Modeste; K Thiombiano; J J Damba; A Ouedraogo; P N Doulkom; I Ouedraogo; A Wandaogo (Wolters Kluwer Medknow Publications, 2023)
Background: Oesophageal stricture is one of the most important and redoubtable complications following caustic ingestions in children. Instrumental dilatation is usually considered the first line of treatment. Aims and Objectives: This study aims to evaluate the outcomes of caustic stenosis treatment when using Lerut dilatators. Materials and Methods: This is a descriptive retrospective study from May 2014 to April 2020. All children under 15 years hospitalised in our department for caustic oesophageal stricture and had a gastrostomy and oesophageal dilatation with insertion of an endless wire were included. Results: A total of 83 patients were included. The sex ratio was 2.2. The mean age was 4 years. The mean time from caustic ingestion to presentation was 90 days. Oesophageal stricture was mostly caused by caustic soda (n = 41) and potash (n = 15). We performed in total 469 dilatations and had only three oesophageal perforations. After a mean follow-up of 17 months, we had 60.2% good results (n = 50) and 7.2% (n = 6) failures. The mortality rate was 13.2% (n = 11). Conclusion: The results of the dilations by Lerut dilatators give encouraging results in our department. It is easy to perform and its complications remain rare. Mortality could be reduced by adequate nutritional support.